2013
DOI: 10.1108/md-02-2013-0084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tidy/messy work environment on human accuracy

Abstract: Purpose -The purpose of this paper is to study the relationship between accuracy and conscientiousness among people working in a tidy/messy work environment. Design/methodology/approach -A laboratory experiment was conducted, where participants performing a simple task in a highly controlled environment were sorted into two different treatments, a tidy or a messy work environment. Findings -The results of this study suggest that conscientious people commit more errors in a messy environment than in a tidy envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
7
1
1
Order By: Relevance
“…In line with previous studies on office workplaces, current research showed that medium-or large-sized home workspaces that are clean and tidy, without noise interruptions, appear to reduce workspace distractions [31], [36], [37]. As the path model indicated, only the size of the workspace directly affected feelings of exhaustion, while the influence of other workspace characteristics on dependent variables were mediated by distractions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with previous studies on office workplaces, current research showed that medium-or large-sized home workspaces that are clean and tidy, without noise interruptions, appear to reduce workspace distractions [31], [36], [37]. As the path model indicated, only the size of the workspace directly affected feelings of exhaustion, while the influence of other workspace characteristics on dependent variables were mediated by distractions.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, conscientious employees were found to be less distracted in their work. As Mateo et al [31] indicated, conscientious people are characterized by their accuracy on the job, especially when working in a tidy work environment. Contradicting to previous research [32], [33] is the finding that conscientious employees are more disengaged from their job.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some civil engineering laboratories do not have much space. If the operator cannot well clean the laboratory, the environment of the civil engineering laboratories will become very messy, which will affect the quality of the operator’s experiments and easily cause accidents [ 84 , 85 ]. Similarly, management is also an invisible driving force for a clean laboratory environment.…”
Section: Discussionmentioning
confidence: 99%
“…The work environment includes work relationships formed between fellow employees and work relations between subordinates and superiors as well as the physical environment where employees work Mateo et al, 2013;Jayaweera, 2015;Saputro, 2016, Pawirosumarto & Gunawan, 2017Adam, & Boateng, 2017;Meriläinen & Kõiv, 2018;Bibi, & Majid, 2018). Research Jayaweera, 2015;Rohail et al, 2017;and Raziq & Maulabakhsh, 2015 has proven that a pleasant work environment is very important to encourage the most productive levels of employee performance.…”
Section: 1mentioning
confidence: 99%